Malawi - Country Economic Memorandum : Policies for Accelerating Growth - World Bank (Washington, DC, 2013)
The report reviews the economic developments in 2003-04, and discusses the main reforms implemented by the government as of March 2003. Since early 2003, the government continued to implement both macro, and structural reforms designed to generate sustainable growth. The economic performance over the past year indicates that these efforts have had mixed results. Despite the adoption of a macroeconomic framework, the government repeatedly failed to reach the set fiscal targets. In addition, the government also implemented, and initiated a number of growth oriented, structural reforms designed to, improve parastatal management, restructure the Agricultural Development and Marketing Corporation (ADMARC) and the food markets, improve the tobacco sector, and, alleviate the impact of HIV/AIDS, in line with the development strategy. In spite of achievements since early 2003, much remains to be done, namely in maintaining fiscal discipline, implementing the next phase of the reforms in maize, tobacco, and agriculture services, including forthcoming reforms to improve the business, and trade environment.